Optimization of annealing temperature from local chromolaena odorata / Nur Hidayah Md Yazid - Md Yazid, Nur Hidayah (Faculty of Applied Sciences, 2014)
Chromolaena odorata belongs to the Asteraceae family which was originally came from Central and South America. In this study the efficiency of a modified CTAB method for DNA extraction from local C. odorata leaves were determined based on their DNA concentration, DNA yield, DNA band and purity. The optimum PCR annealing temperature of local C. odorata was identified by using ITS1 and ITS4 primer amplification. More clear and intact DNA band was produced from extraction using modified CTAB method. The values obtained from the CTAB extraction method for DNA purity, DNA concentration and DNA yield were 1.65±0.06, 101.6+7.638 ng/ uL and 152.5±11.456 ng/mL respectively. The values obtained from the modified CTAB method for DNA purity, DNA concentration and DNA yield were 1.82±0.03, 118.3+7.638 ng/ uL and 177.5+11.456 ng/mL respectively. Modified CTAB extraction method are much more preferable to isolate DNA from local C. odorata due to the presence of reagents such as phenol, polyvinylpyrrolidone, B-mercaptoethanol and also extended treatment of RNase. This study showed that the exact annealing temperature for the isolated DNA from C.odorata with ITS 1 and ITS4 amplification were 65°C and 63°C respectively. Both PCR products obtained were in the range of 250 to 300 base pair in size, which indicates that the amplicon size referred to the primer characteristics.